2006
DOI: 10.28945/3036
|View full text |Cite
|
Sign up to set email alerts
|

ICT Experiences in Two Different Middle Eastern Universities

Abstract: This research explores the impact of technology and culture on higher education in two Arab countries. In western countries where higher education is common, individuals regardless of their gender can meet, communicate, and collaborate at anytime at any place of their choice. This may not be true in Arab countries due to the social, cultural, and religious reasons. We argue that adoption of technology could provide a comparable learning environment to students in these countries. We present results of a case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 9 publications
(3 reference statements)
2
14
0
Order By: Relevance
“…This high level of confidence by students is corroborated by other UAE researchers (Hashem, 2009;Tubaishat et al, 2006), with Shen and Shakir (2009) concluding that "except for a few female students who felt difficulty in using Internet due to lack of knowledge and language skills, the majority (over 90%) feel Internet was "easy to use" " (p. 4). As discussed in this literature review however, there is a commonly held belief that young people are often overconfident in estimating their knowledge and skill level with technology (De Rosa, Cantrell, Hawk, & Wilson, 2006;Lorenzo & Dziuban, 2006;Salaway & Caruso, 2008;Week, 2011).…”
Section: Self-perceived Confidence Skill With Digital Technologiessupporting
confidence: 64%
See 1 more Smart Citation
“…This high level of confidence by students is corroborated by other UAE researchers (Hashem, 2009;Tubaishat et al, 2006), with Shen and Shakir (2009) concluding that "except for a few female students who felt difficulty in using Internet due to lack of knowledge and language skills, the majority (over 90%) feel Internet was "easy to use" " (p. 4). As discussed in this literature review however, there is a commonly held belief that young people are often overconfident in estimating their knowledge and skill level with technology (De Rosa, Cantrell, Hawk, & Wilson, 2006;Lorenzo & Dziuban, 2006;Salaway & Caruso, 2008;Week, 2011).…”
Section: Self-perceived Confidence Skill With Digital Technologiessupporting
confidence: 64%
“…It includes not only arts and letters, but also modes of life, the fundamental rights of the human being, value systems, traditions and beliefs" (UNESCO, 1982 The number of Emirati students applying for tertiary placements more than doubled between 1996 and 2011 (MOHESR, 2011b), with females now making up 70% of Emirati tertiary students (Abdulla & Ridge, 2012). As many researchers have pointed out, there has been a quiet revolution in the legal rights and economic power of Emirati women, with young women experiencing opportunities and freedoms that their mothers and grandmothers could only have dreamed about (AlMarzouqi & Forster, 2011;Bristol-Rhys, 2010;Schvaneveldt, Kerpelman, & Schvaneveldt, 2005;Shakir, Shen, Vodanovich, & Urquhart, 2008;Tubaishat, Bhatti, & ElQawasmeh, 2006;Vodanovich, Urquhart, & Shakir, 2010; It has been suggested that due to socio-economic, cultural and technological changes, traditional family-based social structures are being threatened (Kraidy & Khalil, 2008), that cross-gender communication for young people is likely to be changing (Emdad, Badamas, & Mouakket, 2009;Shen & Shakir, 2009;Skalli, 2006;Sokol & Sisler, 2010), and that traditional political structures are being questioned (Alshare, Grandon, & Badri, 2005;Kraidy, 2007;Kraidy & Khalil, 2008;Samin, 2008 Fandy, 2000;Kraidy & Khalil, 2008;Lynch, 2007;Wheeler, 2000Wheeler, , 2003. Hashem (2009) dispels the theory of homogeneity of Middle Eastern youth when he concludes that "one of the major challenges facing Middle Eastern youth is the possibility of accessing IT tools and knowing how to use them.…”
Section: Social and Cultural Implicationsmentioning
confidence: 99%
“…Also, Llamas-Nistal et al [3] study found that 43 of students out of 52 choose online evaluation rather than traditional evaluation. Moreover, a survey in Jorden University (JU) and Zayed University (ZU) conducted that 59% from JU and 50% from ZU preferred online exams, while 21% from JU and 43% from ZU liked traditional exams [20]. The Sorensen [21] study indicated that student feel that e-assessment play a role in higher education and it adds a value to their learning.…”
Section: The Advantages Of Usinf E-assessmentmentioning
confidence: 99%
“…The social norms dictate how Saudi women behave, for example, Dorter's 1997 study [cited in 6] shows that an explanation given by a female research participant on a distance course demonstrates that the mere presence of men inhibits the learning possibility of women [6] as one woman cites how she felt obliged to leave a distance learning chat room when a male friend of her family entered. Reference [36] agree that there is a strong relationship between culture and learning, which is reflected in the way people prefer to learn and reference [39] noticed that communication between genders is affected by cultural, social and religious inputs. This shows the need to reduce the impact of social and religious beliefs towards the ability of women to learn.…”
Section: Barriersmentioning
confidence: 99%